Performance Evaluation and Economic Viability of Multi-step Basin Type Solar Still for the HotArid Climate of India - Poonia, Surendra; A.K. Singh; Digvijay Singh (Annals of Arid Zone, 2025)
The multi-step basin-type metallic solar still was designed and developed at ICAR-CAZRI in Jodhpur, India. This unit features an absorber area of 1.5 m², with the capability to tilt according to seasonal variations. The previous iteration of this solar still utilized trays constructed from 24-gauge GI sheet, which led to issues such as algae growth and rust, ultimately compromising the unit’s lifespan. In the current design, trays are fabricated from stainless steel to address these concerns. The water temperature in the trays reached approximately 65°C. The performance assessments of the device were conducted by measuring the daily production of distilled water, which ranged from 4.0 to 8.2 liters across different seasons in 2023. The average thermal efficiencies for water heating and distillation were recorded at 20.5% and 34.0%, respectively. Additionally, the economic feasibility and environmental sustainability of the multi-step basin solar still was evaluated. The economic evaluation of the unit demonstrated strong performance, with Internal Rates of Return (IRR) of 143% and 173% and correspondingly short payback periods of 0.80 and 0.65 years. These figures represent the scenarios without and with carbon credit monetization, respectively. These economic indicators demonstrate the system’s viability. Furthermore, this device outperformed conventional reverse osmosis systems in terms of distillate quality. It also has the potential to reduce carbon emissions by approximately 35.1 tonnes over its 15-year lifespan. Consequently, this solar still is well-suited for desalinating saline water in rural arid regions, effectively addressing the need for potable water.